Spatial-Temporal Distribution of Dengue in Banjarmasin, Indonesia From 2016 to 2020 - Nur Afrida Rosvita; Nia Kania; Eko Suhartono; Adi ‪Nugroho; Erida Wydiamala (International Journal of Public Health Science (IJPHS), 2022)
Dengue Hemorrhagic Fever (DHF) is an acute febrile disease caused by four serotypes of dengue virus (DENV) and transmitted by the Aedes aegypti mosquito. This article aims to analyze monthly trends in cases and climates as well as spatial analysis and autocorrelation in 52 urban villages of Banjarmasin City. Laboratory-confirmed dengue cases from 2016 to 2020 were analyzed for trends in malaria cases. Decomposition analysis was performed to assess seasonality. The annual spatial grouping of incidents, identified by Moran's I. The Result shows the annual dengue incidence fell significantly to 72% in 2017 and lasted until 2020. Dengue infection is more common in men with an age range of 15-64 years. The monthly dengue season is highest from January to May along with increased rainfall. The high incidence is spatially clustered which is identified in the east and borders neighboring districts, especially 6 urban villages. A trend and spatially explicit decision support system are needed to support surveillance and control programs in identified high-risk areas to succeed in dengue eradication goals.